What is the upper limit of cement penetration for different femoral hip resurfacing components? - Bitsch, Rudi G.; Obermeyer, Beate J; Rieger, Johannes Sebastian; Jäger, Sebastian; Schmalzried, Thomas P.; Bischel, Oliver E. (The journal of arthroplasty, 2013)
We used a validated femoral resurfacing model to obtain measurements of pressure and temperature and quantify cement distribution as a function of inner geometry and cementing technique of five different femoral hip resurfacing components. The purpose was to investigate if manufacture cementing recommendations are reliable. ASR showed only with the recommended manual cementing technique low cement pressures of 58.0±50.2kPa and low interface temperatures of 33.3±4.1°C. BHR had large cement defects of 10.4±1.1mm. Conserve Plus caused the smallest cement penetration depths of 2.9±0.6mm. Durom was tolerant against changes of the cementing technique but showed the widest spread of temperature data 42.8±7.0°C. ReCap showed the highest risk for incomplete seating with a cement mantle thickness of 4.3±0.9mm. Polymerization heat did not exceed the threshold of 45°C with a cement penetration depth of less than 4.2mm in any circumstances of this study.
Available online 14 December 2012
Gesehen am 26.11.2020